2022
DOI: 10.1038/s41586-022-05355-z
|View full text |Cite|
|
Sign up to set email alerts
|

Global hotspots of salt marsh change and carbon emissions

Abstract: Salt marshes provide ecosystem services such as carbon sequestration1, coastal protection2, sea-level-rise (SLR) adaptation3 and recreation4. SLR5, storm events6, drainage7 and mangrove encroachment8 are known drivers of salt marsh loss. However, the global magnitude and location of changes in salt marsh extent remains uncertain. Here we conduct a global and systematic change analysis of Landsat satellite imagery from the years 2000–2019 to quantify the loss, gain and recovery of salt marsh ecosystems and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 75 publications
0
56
1
1
Order By: Relevance
“…As an example, Bishop-Taylor et al 6 highlighted in their Figure 3 that the sun-synchronous overpass of Landsat can be spatially biased in capturing tidal cycles across the Australia coastline. This could affect Campbell et al's 1 estimations of loss and gain in regions such as the northern and southern Australian coasts (Campbell et al 1 : Figure 1b).…”
Section: Technical Notementioning
confidence: 96%
See 4 more Smart Citations
“…As an example, Bishop-Taylor et al 6 highlighted in their Figure 3 that the sun-synchronous overpass of Landsat can be spatially biased in capturing tidal cycles across the Australia coastline. This could affect Campbell et al's 1 estimations of loss and gain in regions such as the northern and southern Australian coasts (Campbell et al 1 : Figure 1b).…”
Section: Technical Notementioning
confidence: 96%
“…In a recent study, Campbell et al 1 conducted a large-scale change analysis using Landsat satellite data from 2000 to 2019 to estimate global changes in the salt marsh ecosystem coverage and their impact on blue carbon stock. Based on 20-yr satellite change detection, they reported that more than 1400 km 2 of marshes had been lost, with the USA and Russia contributing 64% of the total loss.…”
Section: Technical Notementioning
confidence: 99%
See 3 more Smart Citations